New-onset headache after percutaneous atrial septal defect closure - Debasree Gangopadhyay; Mahua Roy (Wolters Kluwer Medknow Publications, 2022)
Background : Percutaneous closure of atrial septal defect (ASD) is a well-established procedure both in children and adults with very good long-term outcomes. Migraine headache (MHA) can be precipitated after ASD device closure and the mechanism is not fully understood. Methods : We reviewed medical records of all patients undergoing ASD device closure from January 2015 to January 2021 for new onset headache after the procedure. Diagnosis of migraine was established by guidelines of the International Headache Society. Results : Out of 325 patients undergoing ASD device closure, five patients (1.5%) of various age groups (range 3.5-35 years) complained of severe migraine-like headaches within 2 weeks of the procedure. MHA was reported exclusively by females. All the patients were treated with oral paracetamol for the management of headaches. Three of 5 (60%) patients had a positive family history of migraine. Three patients reported complete disappearance of symptoms within 4-6 months. While two others (40%) had ongoing symptoms at 6 months follow-up. Conclusions : MHA can be precipitated after ASD device closure. The risk is specifically high in females with a family history of migraine. Dual antiplatelet drugs for the first 3 months after device closure may prevent such episodes. Prospective studies are needed to establish the universal role of dual antiplatelet drugs after ASD device closure.